USVs‐Sim: A general simulation platform for unmanned surface vessels autonomous learning. (15th September 2021) - Wang, Wei; Zhang, Han; Li, Yang; Zhang, Zhenyu; Luo, Xiangfeng; Xie, Shaorong
Abstract: Unmanned surface vessels (USVs) have been fully used in the civilian and military fields in recent years, which dramatically expands protective capability and detection range. However, the marine environment's complexity and variability make that verification of various advanced USVs control algorithms face high costs and high risks. In this article, we present USVs‐Sim, a novel high‐fidelity general simulation platform for USVs autonomous navigation data generation and control strategy testing. USVs‐Sim is a collection of high‐level extensible modules that allows the rapid development and testing of USVs configurations and facilitates the construction of complex ocean scenarios. USVs‐Sim supports the steering or thrusting limits of USVs, as well as unique dynamics profiles. The platform can specify specific USVs sensor systems and change the time of day and weather conditions to generate robust data. USVs‐Sim facilitates training of deep‐learning algorithms by enabling data export from USVs sensors, including vision data, lidar, relative positions of ocean targets. Therefore, USVs‐Sim allows for the rapid prototyping, development, and testing of USVs autonomous control algorithms in a complex marine environment. In this article, we detail the general simulation platform and testing several representative USVs intelligent control algorithms on the platform.